Impact of Disability, Psychological Status, and Comorbidity on Health-Related Quality of Life Perceived by Subjects with Obesity - Donini, Lorenzo Maria (Obes Facts, 2020)
Obesity is a rapidly growing public health problem affecting an increasing number of countries worldwide and creating substantial financial and health burdens. Obesity has a negative impact on health-related quality of life (HRQoL) with reference to physical and mental health status, social relationships, and economic factors. The aim of the present study is to investigate the association of number of comorbidities, psychological status, and disability level with HRQoL in a sample of subjects with obesity. METHODS: A total of 273 subjects with obesity (199 women and 74 men) were recruited. Medical history and anthropometric measurements were carried out. The Italian version of the Laval questionnaire, the TSD-OC (SIO test for obesity-related disabilities), and SCL-90 (Symptom Checklist-90) tests were administered. The association between HRQoL (global and different domains scores of the Laval questionnaire − dependent variable) and age, body mass index (BMI), comorbidity, TSD-OC, and SCL-90 was analysed using a stepwise linear regression model. RESULTS: BMI, disability (TSD-OC global score), and psychological symptoms (SCL-90 global severity index) were found to be the main determinants of HRQoL. Single domains of HRQoL (symptoms, activity/mobility, personal hygiene/clothing, emotions, social interaction, and sexual life) showed different patterns of associations with each domain of the Laval questionnaire. BMI, pain, and social life disruptions were found to be significantly associated with most of the HRQoL domains while age, comorbidities, psychological problems (depression, interpersonal symptoms, somatization), and disability were associated with only some domains of the Laval questionnaire. Education, psychological symptoms (obsessive-compulsive, anxiety, hostility, phobic anxiety, paranoid ideation), and disability domains (stiffness, housework, outdoor activities, occupational activities) were not associated with any of the dimensions of the Laval questionnaire. DISCUSSION/CONCLUSION: The present study identified key determinants of QoL in subjects with obesity, which could help in refining the multidimensional diagnostic assessment of obesity as well as designing more effective interventions to improve HRQoL in these patients.